2020
DOI: 10.3390/cryst10100944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3D Representative Volume Element (RVE) Thickness on Stress and Strain Partitioning in Crystal Plasticity Simulations of Multi-Phase Materials

Abstract: Crystal plasticity simulations help to understand the local deformation behavior of multi-phase materials based on the microstructural attributes. The results of such simulations are mainly dependent on the Representative Volume Element (RVE) size and composition. The effect of RVE thickness on the changing global and local stress and strain is analyzed in this work for a test case of dual-phase steels in order to identify the minimal RVE thickness for obtaining consistent results. 100×100×100 voxel representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…It is observed that the damage initiation in the case of 2D-RVE occurs at a global strain of ≈ 6% earlier in comparison with damage initiation in the case of 3D-RVE. This trend is exciting and probably occurs due to the higher contrast of accumulated strain in the case of 2D, as reported by earlier researchers [17,23]. These observations help generalize that damage initiation in 2D-RVE occurs at ≈ 6% less global strain than the damage initiation in 3D-RVE.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…It is observed that the damage initiation in the case of 2D-RVE occurs at a global strain of ≈ 6% earlier in comparison with damage initiation in the case of 3D-RVE. This trend is exciting and probably occurs due to the higher contrast of accumulated strain in the case of 2D, as reported by earlier researchers [17,23]. These observations help generalize that damage initiation in 2D-RVE occurs at ≈ 6% less global strain than the damage initiation in 3D-RVE.…”
Section: Discussionsupporting
confidence: 84%
“…The mesh density in all the generated RVEs is . In the previous study by Qayyum et al [ 23 ] it has already been established that the 3D RVEs with size comprising of grains behave isotropically when loaded in any direction. Due to an overall neutral orientation distribution function (ODF) selection during RVE generation, a complete random orientation distribution of the grains is observed.…”
Section: Numerical Simulation Model Developmentmentioning
confidence: 98%
See 3 more Smart Citations